Productos y servicios financieros a gran escala para la microempresa colombiana (2005)
This work is based on a previously proposed model by the author; this one aims to the possibility of selling financial products and services on great scale to the microenterprises by commercial banks. This model is also the result of a revision of some part of the available literature related to this subject and a personal contribution of the author. This model proposes that the great commercial banks are the ones called to sell financial products and services to the microenterprises on great scale, implementing microenterprise banking and penetrating this segment of the market or, as it is called in the international marketing slang, doing downscaling. In a previous work, a set of critical variables was identified and was also established the way how these variables must be defined in the commercialization of financial products and financial services to have a considerable increase in the probability of being viable and sustainable in the time. In this report, the second one of three reports related to this subject, the results corresponding to the pre-feasibility study for the project “Financial products and services on great scale for the colombian microenterprise” are analyzed, based on the proposed model and following the methodology for the study of projects of the United Nations Industrial Development Organization (UNIDO).